KONTRIBUSI ORANG TUA DALAM PEMBELAJARAN LURING SELAMA PANDEMI COVID-19 PADA SISWA KELAS III B DI SDN 136/II SUMBER HARAPAN - feni rahmawati silvi (Consilium: Education and Counseling Journal, 2021)
This research is a problem in offline learning. Where some students who are active while attending lessons at school they get good learning outcomes but when given offline learning assignments they get low learning outcomes. This study aims to find out about the form of parental contribution in offline learning during the covid-19 pandemic. This research is a descriptive qualitative research type, conducted in class IIIB SDN 136/II Sumber Harapan in the even semester of the 2020/2021 academic year. Sources of data in this study were parents and students of class IIIB. Data collection techniques used in this study are interview methods and documentation methods. Data analysis is done by collection, reduction, display and verification. The results obtained are the form of parental contributions consisting of four contributions, namely: As caregivers and educators including scheduling children's study time and reminding children to do school assignments, as mentors including accompanying children while studying and overcoming children's difficulties in offline learning, as a motivator including parents can motivate by giving praise or gifts for positive things that have been done by children, as facilitators including parents can provide facilities such as books, worksheets, android mobile phones, internet quota. The obstacles faced by parents in offline learning during the COVID-19 pandemic are: parents do not understand the content of the subject matter, parents have little time to accompany their children to study, facilities are inadequate or limited, and children are difficult to teach by their parents.